Fishermen Welfare Level in Torosiaje Laut Village - Wisna D Onte; Aziz Salam; Zhulmaydin Chair Fachrussyah (The NIKe Journal, 2018)
The purpose of this study aims to determine the level of welfare of the fishermen of Torosiaje Laut Village, Popayato District, Pohuwato Regency, including calculating the household income of fishermen and fishermen household expenses. The study was conducted in May to June 2016. The research method used was descriptive method. The average per capita income of fishermen per year is IDR. 6.180,000 and per capita expenditure per year is IDR. 1,870,200 and the conditions of residence and facilities are complete, health services, education and transportation are easily accessible by fishing communities, thus it can be said that this fisherman household in Desa Torosiaje Laut can be said to be prosperous. Keywords: welfare; fishermen; family.